Team management strategies for DevOps - Ferreira, Rui Maurício da Cunha (2022)
In an increasingly digital market, and where the time to market is shorter and the quality and reliability more relevant, it is imperative that software development teams can organize themselves in order to provide a faster reaction to the market with more reliability. DevOps intends to eliminate the existence of silos (Development and Operations) and streamline the software production, declining waste and difficulties in its construction, increasing productivity and developing better products with a focus on client satisfaction. Nevertheless, the joining of teams around the same goal causes key managing challenges, namely the management of conflicts and information sharing between teams. The way that these challenges are managed can interfere with the successful implementation of DevOps philosophy. Though a Case Study, the research goal is to study the best team management strategies that help to reduce the appearance of conflicts and enhance information sharing in the context of DevOps implementation, increasing effectiveness in those teams. As a result, this research brings some strategies to facilitate the DevOps team management and reinforces the importance of managing conflicts, processes, tasks and information well.